Research into the possibilities of digitalization in publishing (Herald of Journalism, 2024)
The authors of the article differentiate innovations in publishing. Defines the evolutionary features of publishing in the period of digitalization. Conducts an overview of the digitalization process in foreign and domestic publishing, examines the search and opportunities in publishing.The scientific article examines the know-how in publishing a literary book and the achievements of publishing transformed into a digital system. New concepts in publishing are studied and their impact is described. Comparative analysis of the digitization process and the experience of book publishing in domestic publications.The main purpose of the scientific article is to show the know–how in publishing, to consider new opportunities for the development of fiction, taking into account statistical data on literary books, as well as to demonstrate the results of technological modernization in terms of digitalization in publishing.To achieve these aims, the research addresses several key tasks:   a) A detailed description of the transition process from traditional book formats to a digitized system, including an overview of innovative methods for publishing literary works;  b) An examination of the professional challenges encountered in literary book publication that have arisen due to digitization; c) An analysis of annual output statistics from various publishing houses; d) An exploration of the roles and potential strategies for literary publishing agents; e) A critical assessment of different models employed in book publishing.This structured approach seeks to contribute significantly to the existing body of knowledge regarding digitalization's transformative role in the publishing industry and its implications for publication of literary works.In the final part of the scientific work, the works that have achieved success in the publishing business of the country are identified, and the main problems in this area are summarized. It also suggests ways to make a literary book more liquid for the reader.The results of the scientific research analyzed the current problems considered in the field of publishing and media. Specific proposals related to the search for domestic publishers in the book business, innovations in the introduction of foreign experience, as well as current problems in publishing will be announced. Focusing on the most common methods of arousing the interest of readers of the book, the directions of domestic publishing houses are comparatively analyzed. The ways of solving urgent problems of domestic book production are considered. In the pursuit of innovation and mastering world experience, the search for the "Mazmundama" foundation in recent years is positively assessed.
Keywords: publishing, digitalization, literary agent, sammari method, segment, generation Z, book industry.